Double magnetic tunnel junctions with a switchable assistance layer for improved spin transfer torque magnetic memory performance. Issue 33 (10th August 2021) - Sanchez Hazen, Daniel; Auffret, Stéphane; Joumard, Isabelle; Vila, Laurent; Buda-Prejbeanu, Liliana D.; Sousa, Ricardo C.; Prejbeanu, Lucian; Dieny, Bernard
Abstract : This paper reports the first experimental demonstration of a new concept of double magnetic tunnel junctions comprising a magnetically switchable assistance layer. Abstract : This paper reports the first experimental demonstration of a new concept of double magnetic tunnel junctions comprising a magnetically switchable assistance layer. These double junctions are used as memory cells in spin transfer torque magnetic random access memory (STT-MRAM) devices. Their working principle, fabrication and electrical characterization are described and their performances are compared to those of reference devices without an assistance layer. We show that thanks to the assistance layer, the figure of merit of STT-MRAM cells can be increased by a factor of 4 as compared to that of STT-MRAM based on conventional stacks without the assistance layer. A detailed discussion of the results is given supported by numerical simulations. The simulations also provide guidelines on how to optimize the properties of the assistance layer to get the full benefit from this concept.